REVISITING THE HUMAN RIGHT TO WATER IN CONTEMPORARY INTERNATIONAL LAW (UUM Journal of Legal Studies, 2020)
The right to water has passed through many steps until it has received a full legal adoption in the international human rights law and international water law. However, there are many parties which feel that the right to water should not stand on its own as it complicates the present legal framework for international human rights. This paper examined, based on qualitative research approach, several impediments in legislating water as a human right within the purview of relevant international human rights conventions, taking into account the United Nations (UN) Agenda 2030 for Sustainable Development Goals No. 3: Good Health and Well-being and Goal No. 6: Clean Water and Sanitation. The study indicates that human rights notions have been gaining influential rule in international water law, notably human right to water, which has been recognized by the UN General Assembly and the Human Rights Council (HRC). This study however concludes that despite efforts to deny the legal basis of the right to water as one of the soft law, this right remains as a basic human right and should be respected by all countries.